Analysis of The Effect of Organizational Trust on Employee Commitment Mediated by Employee Engagement - Salshabilla Devy Rachmaningrum; Dharmayanti Pri Handini (Optima Science, 2024)
This study aims to determine the effect of Organizational Trust on Employee Commitment with Employee Engagement as a Mediation Variable. The population in this study is all employees with civil servant status who work at the Malang City Industrial and Trade Cooperative Office. This study uses a type of explanatory research using quantitative approach methods that are easier to measure, easy to set research goals, easy to establish populations and samples, and easy to compile questionnaires, and to determine whether the theory used to predict it is correct or not. Sampling technique with Proportionate Stratified Random Sampling with a total of 67 respondents. Data collection methods in the form of questionnaires and data analysis techniques using path analysis. And the data is processed through Smart Partial Least Square (PLS) software. The results of the hypothesis test, the relationship of organizational trust to employee commitment through employee engagement has a significant effect in mediating the effect of organizational trust on employee commitment. The results of the organizational trust hypothesis test on positive and significant employee commitment and organizational trust on employee engagement have a positive and significant effect. Thus, the results of the hypothesis test show that organizational trust has a significant impact not only directly on employee commitment, but also through employee engagement mediation. This shows that the importance of building good organizational trust in order to increase maximum employee commitment and increase employee commitment in the organization, as well as increase employee engagement with the organization.